DISTRIBUTION OF ULCERATIVE GLOSSITIS OF CATTLE IN SELECTED FARMS IN POLTAVA REGION - Канівець, Н. С. (Scientific Progress & Innovations, 2015)
According to the results of the research in some farms in Poltava district Poltava region we found that ulcerative glossitis spread among cows ranged from 0 to 57,9 % in cows, and from 0 to 57,2 % – in calves, which shows that the cows sick more often than calves. The findings and analysis of the literature show widespread ulcerative glossitis of cattle both in Ukraine and abroad.